Formation kinetics of radiolytic lipid products in model food–lipid systems with gamma irradiation. (1st July 2021) - Taghvaei, Mostafa; Tonyali, Bade; Sommers, Christopher; Ceric, Olgica; Linghu, Ziyi; Smith, Joseph Scott; Yucel, Umut
Abstract: Irradiation processes can change the lipid composition of foods. The major lipid radiolysis products are known to be 2‐alkylcyclobutanones and hydrocarbons, the formation kinetics of which is determined by the chemical nature of the inherent lipids. This information can be used to evaluate the irradiation history of lipid‐rich foods. A solid‐phase microextraction (SPME)‐assisted gas chromatography–mass spectrometry (GC–MS) technique was used to study the formation of volatile hydrocarbons and 2‐dodecylcyclobutanone (2‐DCB), a cyclobutanone formed from the esters of palmitic acid, in irradiated (0–50 kGy) tripalmitin and chicken fat. Thirty‐three volatile compounds (hydrocarbons, aldehydes, ketones) increased with irradiation dose to varying extents. Six major lipid radiolysis products were selected to analyze their formation kinetics: tridecane, 1‐tetradecene, tetradecane, 1‐pentadecene, pentadecane, and 2‐DCB. The concentration of the selected compounds increased linearly with irradiation dose following zeroth‐order kinetics, except for tridecane and tetradecane in tripalmitin, formation of which followed first‐order kinetics. The formation rate of hydrocarbons was higher in tripalmitin than in chicken fat (5× higher for pentadecane), while 2‐DCB formed faster (3.5×) in chicken fat than in tripalmitin. This difference was related to the diversity in the natural fatty acid composition of chicken fat as compared to the homogeneous structure of tripalmitin. The results of this study indicate that the concentrations of palmitic acid radiolysis products linearly increase with irradiation dose in general to offer potential to back‐trace irradiation dose in lipid‐rich foods.